Utilization and Complications of Catheter Ablation for Atrial Fibrillation in Patients With Hypertrophic Cardiomyopathy - Rozen, Guy; Elbaz‐Greener, Gabby; Marai, Ibrahim; Andria, Nizar; Hosseini, Seyed Mohammadreza; Biton, Yitschak; Heist, E. Kevin; Ruskin, Jeremy N.; Gavrilov, Yulia; Carasso, Shemy; Ghanim, Diab; Amir, Offer (Journal of the American Heart Association, 2020)
Background Atrial fibrillation (AF) is common and bears a major clinical impact in patients with hypertrophic cardiomyopathy (HCM). We aimed to investigate the use and real-world safety of catheter ablation for AF in patients with HCM. Methods and Results We drew data from the US National Inpatient Sample to identify cases of AF ablation in HCM patients between 2003 and 2015. Sociodemographic and clinical data were collected, and incidence of catheter ablation complications, mortality, and length of stay were analyzed, including trends between the early (2003-2008) and later (2009-2015) study years. Among a weighted total of 1563 catheter ablation cases in patients with HCM, the median age was 62 (interquartile range, 52-72), 832 (53.2%) were male, and 1150 (73.6%) were white. The average annual volume of AF ablations in patients with HCM doubled between the early and the later study period (79-156). At least 1 complication occurred in 16.1% of cases, and the in-hospital mortality rate was 1%. Cardiac and pericardial complications declined from 8.8% to 2.3% and from 2.8% to 0.9%, respectively, between the early and the later study years ( <0.01). Independent predictors of complications included female sex (odds ratio [OR], 4.81; 95% CI, 2.72-8.51), diabetes mellitus (OR, 6.57; 95% CI, 2.68-16.09) and obesity (OR, 3.82; 95% CI, 1.61-9.06). Conclusions Despite some decline in procedural complications over the years, catheter ablation for AF is still associated with a relatively high periprocedural morbidity and even mortality in patients with HCM. This emphasizes the importance of careful clinical consideration, by an experienced electrophysiologist, in referring patients with HCM for an AF ablation.